Soft magnetic alloy powders, magnetic cores, magnetic components and electronic devices
By adopting soft magnetic alloy powder optimized with specific composition and process, the problem of insufficient magnetic permeability in the prior art is solved, and efficient core performance improvement is achieved, which is suitable for high-frequency and efficient magnetic components in electronic equipment.
Patent Information
- Application Number
- CN202011464043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-08
- Filing Date
- 2020-12-14
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-12-14
AI Technical Summary
The prior art is difficult to provide soft magnetic alloy powders with good magnetic permeability to improve the performance of magnetic cores in electronic devices, especially in terms of reduced energy loss and improved power efficiency.
Using a soft magnetic alloy powder of the composition of Co(1-(α+β)X1αX2β)(1-(a+b+c+d+e+f))MaBbPcSidCreSf, combined with a gas atomization method, and controls the components and process parameters such as spherical degree, amorphization rate and pressure application, optimize particle shape and structure, and improve relative magnetic permeability and filling rate.
A soft magnetic alloy powder with high relative magnetic permeability and high filling rate is achieved, reducing the proportion of special-shaped particles, improving the performance of the magnetic core, and suitable for efficient magnetic components in electronic equipment.
Smart Images

Figure CN113053610B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to soft magnetic alloy powder, magnetic core, magnetic component and electronic equipment. Background Art
[0002] In recent years, there has been a demand for low power consumption and high efficiency in electronics, information and communication equipment, especially electronic equipment. In addition, the above demand is even stronger towards a low-carbon society. Therefore, there is also a demand for reducing energy loss and improving power efficiency in the power supply circuit of electronics, information and communication equipment, especially electronic equipment.
[0003] Therefore, in order to reduce energy loss and improve power supply efficiency, it is necessary to obtain a soft magnetic alloy powder that has excellent soft magnetic properties and can increase the filling rate when used in a magnetic core.
[0004] Patent Document 1 describes a soft magnetic metal powder having improved Wardle sphericity, and also describes that an excellent power inductor can be manufactured by improving the sphericity.
[0005] Patent Document 2 describes a Co-based amorphous alloy ribbon and states that the magnetic permeability and squareness ratio are improved by setting the S content to 30 ppm or less and the Al content to 40 ppm or less.
[0006] In addition, as a method of filling the soft magnetic alloy powder at a high density, the methods described in Patent Documents 3 and 4 are known to be effective.
[0007] Patent Document 3 describes that an inductor having excellent relative magnetic permeability can be produced by using soft magnetic alloy powder with high sphericity.
[0008] Patent Document 4 describes that by using two kinds of particles having different particle diameters and setting the particle diameter ratio of the two kinds of particles within a specific range, the particles can be packed at a high density and the relative magnetic permeability can be improved.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2016-25352
[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 3-173750
[0013] Patent Document 3: Japanese Patent Application Publication No. 2010-212442
[0014] Patent Document 4: Japanese Patent Application Publication No. 2011-192729 Summary of the invention
[0015] Technical problem to be solved by the invention
[0016] An object of the present invention is to provide a soft magnetic alloy powder capable of obtaining a magnetic core having good magnetic permeability.
[0017] Technical solutions for solving technical problems
[0018] In order to achieve the above-mentioned object, the soft magnetic alloy powder involved in the first aspect of the present invention has a composition formula (Co (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c Si d Cr e S f (atomic ratio) of the main components, among which,
[0019] X1 is one or more selected from Fe and Ni,
[0020] X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C and rare earth elements,
[0021] M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V,
[0022] 0<a≤0.140,
[0023] 0.160<b≤0.250,
[0024] 0≤c≤0.200,
[0025] 0≤d≤0.250,
[0026] 0≤e≤0.030,
[0027] 0≤f≤0.010,
[0028] 0.160<b+c+d+e+f≤0.430,
[0029] 0.500<1-(a+b+c+d+e+f)<0.840,
[0030] α ≥ 0,
[0031] β ≥ 0,
[0032] 0≤α+β<0.50,
[0033] The soft magnetic alloy powder has a glass transition temperature Tg and a melting point Tm.
[0034] And 900℃≤Tm≤1200℃.
[0035] The average circularity of the powder particles contained in the soft magnetic alloy powder according to the first aspect of the present invention may be 0.93 or more, and the cumulative number ratio of the powder particles from the lowest circularity to 0.50 may be 2.0% or less.
[0036] The average circularity of the powder particles contained in the soft magnetic alloy powder according to the first aspect of the present invention may be 0.95 or more, and the cumulative number ratio of the powder particles from the lowest circularity to 0.50 may be 1.5% or less.
[0037] In the soft magnetic alloy powder according to the first aspect of the present invention, a value obtained by dividing the content ratio of Co by the content ratio of B may be greater than 2.000 and less than 5.000.
[0038] The soft magnetic alloy powder according to the first aspect of the present invention may be amorphous.
[0039] The soft magnetic alloy powder according to the first aspect of the present invention may have nanocrystals.
[0040] In order to achieve the above object, the soft magnetic alloy powder according to the second aspect of the present invention has a composition formula (Co (1-(α+β)) X1 α X3 β ) (1-(a+b+c+d+e)) M a B b P c Si d Cr e (atomic ratio) of the main components, among which,
[0041] X1 is one or more selected from Fe and Ni,
[0042] X3 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C, S and rare earth elements,
[0043] M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V,
[0044] 0<a≤0.140,
[0045] 0.160<b≤0.250,
[0046] 0≤c≤0.200,
[0047] 0≤d≤0.250,
[0048] 0≤e≤0.030,
[0049] 0.160<b+c+d+e≤0.430,
[0050] 0.500<1-(a+b+c+d+e)<0.840,
[0051] α ≥ 0,
[0052] β ≥ 0,
[0053] 0≤α+β<0.50,
[0054] A pressure X is applied to the soft magnetic alloy powder. P The coercivity at H , we will use the least squares method to find X P With Y H The straight line obtained by linear approximation of the relationship is represented by Y H =kX P When +l, k (unit: Oe / MPa) is 0≤k≤0.00100.
[0055] The soft magnetic alloy powder according to the second aspect of the present invention may have a structure including amorphous matter.
[0056] The soft magnetic alloy powder according to the second aspect of the present invention may have a structure including heteroamorphous.
[0057] The soft magnetic alloy powder according to the second aspect of the present invention may have a structure including nanocrystals.
[0058] The following description is common to the soft magnetic alloy powder according to the first aspect and the soft magnetic alloy powder according to the second aspect.
[0059] The amorphization ratio X of the soft magnetic alloy powder according to the present invention may be 85% or more.
[0060] The magnetic core according to the present invention contains the above-mentioned soft magnetic alloy powder.
[0061] The magnetic component according to the present invention contains the above-mentioned soft magnetic alloy powder.
[0062] The electronic device according to the present invention contains the above-mentioned soft magnetic alloy powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is an example of a pattern obtained by X-ray crystal structure analysis.
[0064] Figure 2 It is through Figure 1An example of a pattern obtained by performing graph fitting on a graph of .
[0065] Figure 3 This is the observation result of Morphologi G3 of powder particles with high roundness.
[0066] Figure 4 These are the observation results of Morphologi G3 of powder particles with low roundness.
[0067] Figure 5 This is a graph showing the relationship between circularity and cumulative number ratio.
[0068] Figure 6 Yes means Figure 5 A graph of the portion with a circularity of 0.4 to 0.6.
[0069] Figure 7 It is a graph showing the melting point Tm.
[0070] Figure 8 It is a graph showing the glass transition temperature Tg and the crystallization start temperature Tx.
[0071] Fig. 9 Yes means Figure 8 A graph of a portion having a temperature of 450°C to 600°C.
[0072] Fig. 10A It is a schematic diagram of a metal powder manufacturing apparatus.
[0073] Fig. 10B yes Fig. 10A An enlarged schematic diagram of the main parts.
[0074] Explanation of symbols
[0075] 1, 2: particle shape measurement results; 10: atomizing device; 20: molten metal supply part; 21: molten metal; 21a: dripping molten metal; 30: cooling part; 36: cooling liquid introduction part; 38a1: outer convex part; 50: cooling liquid flow. DETAILED DESCRIPTION
[0076] Hereinafter, embodiments of the present invention will be described.
[0077] (First Embodiment)
[0078] The soft magnetic alloy powder of this embodiment has a composition formula (Co (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c Si d Cre S f (atomic ratio) of the main components of the soft magnetic alloy powder, wherein
[0079] X1 is one or more selected from Fe and Ni,
[0080] X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C and rare earth elements,
[0081] M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V,
[0082] 0<a≤0.140,
[0083] 0.160<b≤0.250,
[0084] 0≤c≤0.200,
[0085] 0≤d≤0.250,
[0086] 0≤e≤0.030,
[0087] 0≤f≤0.010,
[0088] 0.160<b+c+d+e+f≤0.430,
[0089] 0.500<1-(a+b+c+d+e+f)<0.840,
[0090] α ≥ 0,
[0091] β ≥ 0,
[0092] 0≤α+β<0.50,
[0093] The soft magnetic alloy powder has a glass transition temperature Tg and a melting point Tm.
[0094] And 900℃≤Tm≤1200℃.
[0095] Generally speaking, the soft magnetic alloy powder having a composition containing more Co has a higher relative magnetic permeability than the soft magnetic alloy powder having a composition containing more Fe. In addition, the corrosion resistance and electrical resistance of the soft magnetic alloy powder having a composition containing more Co are easily increased, and the dielectric loss is easily reduced. Moreover, the melting point of the soft magnetic alloy powder having a composition containing more Co is lower than that of the soft magnetic alloy powder having a composition containing more Fe. As a result, when the soft magnetic alloy powder is produced by an atomization method such as gas atomization described later, the atomization temperature is easily lowered. In addition, the melting point of the molten liquid containing the soft magnetic alloy before atomization is usually the same as the melting point of the soft magnetic alloy powder obtained by atomization.
[0096] The soft magnetic alloy powder according to the present embodiment has the above-mentioned composition, and has the glass transition temperature and the above-mentioned melting point, so that the particle shape of the powder particles can be made good. Specifically, by having the above-mentioned composition, and having the glass transition temperature and the above-mentioned melting point, a soft magnetic alloy powder containing powder particles with a high average sphericity can be obtained. In addition, a soft magnetic alloy powder with a small number of powder particles having a low roundness, that is, a soft magnetic alloy powder with a small proportion of irregular particles can be obtained.
[0097] Therefore, the soft magnetic alloy powder according to the present embodiment includes the powder particles of the above-mentioned particle shape, and thus can improve the filling rate of the magnetic core etc. using the soft magnetic alloy powder, and can improve various properties such as the relative magnetic permeability of the magnetic core etc. Hereinafter, the powder particles may be simply referred to as particles.
[0098] In addition, when the soft magnetic alloy powder of the present embodiment is heat treated, nanocrystals with a grain size of less than 100 nm or less than 50 nm are easily precipitated. Whether nanocrystals are included and whether amorphous is included can be confirmed by XRD. In addition, TEM can also be used to confirm.
[0099] The structure containing amorphous is a structure having only amorphous or a structure containing heterogeneous amorphous. The structure containing heterogeneous amorphous is a structure in which initial microcrystals exist in amorphous. Among them, the average crystal grain size of the initial microcrystals is not particularly limited, and the average crystal grain size can be 0.3nm or more and 10nm or less. In addition, the amorphous rate of the structure containing amorphous that can be confirmed by XRD is 85% or more. Among them, whether it is a structure having only amorphous or a structure containing heterogeneous amorphous can be confirmed by TEM. The structure containing nanocrystals is a structure mainly containing nanocrystals. In the structure containing crystals (nanocrystals), the amorphous rate that can be confirmed by XRD is less than 85%. In addition, the average crystal grain size of the nanocrystals in the structure containing nanocrystals is 5nm or more and 100nm or less. In the structure containing heterogeneous amorphous and the structure containing nanocrystals, there is no crystal with a crystal grain size exceeding 100nm. Among them, in the present embodiment, the soft magnetic alloy powder preferably has a structure containing amorphous, and particularly preferably has a structure containing heterogeneous amorphous.
[0100] In this embodiment, the soft magnetic metal powder having an amorphization rate X of 85% or more represented by the following formula (1) has a structure having only amorphous or a structure including heterogeneous amorphous, and the soft magnetic metal powder having an amorphization rate X of less than 85% has a structure including crystals.
[0101] X=100-(Ic / (Ic+Ia)×100)…(1)
[0102] Ic: Crystalline scattering integrated intensity
[0103] Ia: Amorphous scattering integrated intensity
[0104] For soft magnetic metal powder, X-ray crystal structure analysis is performed using XRD to identify the phase, and the peaks of crystallized Fe or compounds (Ic: crystalline scattering integrated intensity, Ia: amorphous scattering integrated intensity) are read. The crystallization rate is estimated based on the peak intensity, and the amorphous rate X is calculated using the above formula (1). The calculation method is described in more detail below.
[0105] The soft magnetic metal powder according to this embodiment was analyzed by X-ray crystal structure analysis using XRD, and the Figure 1 The graph shown in Figure 2 is used to fit the Lorentz function of the following formula (2) to obtain Figure 2 The crystal component pattern α showing the integrated intensity of crystalline scattering is shown in FIG. c , Amorphous component pattern α showing the integrated intensity of amorphous scattering a and the pattern α after combining them c+a The amorphization rate X is calculated using the above formula (1) based on the crystalline scattering integrated intensity and amorphous scattering integrated intensity of the obtained pattern. The measurement range is the range of diffraction angle 2θ = 30° to 60° in which the halo from the amorphous can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated by the Lorentz function is within 1%.
[0106]
[0107] h: peak height
[0108] u: peak position
[0109] w: half width
[0110] b: background height
[0111] In addition, when the soft magnetic alloy powder of the present embodiment includes nanocrystals, each particle includes a plurality of nanocrystals. That is, the particle size of the soft magnetic alloy powder described below is different from the crystal particle size of the nanocrystals.
[0112] Hereinafter, each component of the soft magnetic alloy powder according to the present embodiment will be described in detail.
[0113] M is one or more selected from the group consisting of Nb, Hf, Zr, Ta, Mo, W, Ti and V.
[0114] The content (a) of M satisfies 0<a≤0.140. It may also satisfy 0.001≤a≤0.140. In addition, it may also satisfy 0.003≤a≤0.140, and it may also satisfy 0.040≤a≤0.100. When M is not contained, it is difficult for the soft magnetic alloy powder to have a glass transition temperature Tg. As a result, the circularity of the particles is easily reduced, and the relative magnetic permeability decreases. When a is too large, the melting point Tm of the soft magnetic alloy powder is easily reduced. As a result, the circularity of the particles is easily reduced, the proportion of irregular particles in the soft magnetic alloy powder increases, and the relative magnetic permeability decreases. In addition, the saturation magnetic flux density is easily reduced. Among them, from the viewpoint of easily reducing the coercive force, 0.010≤a≤0.140 is preferred.
[0115] The content of B (b) satisfies 0.160<b≤0.250. It can also satisfy 0.180≤b≤0.250. When b is too small, the melting point Tm of the soft magnetic alloy becomes too high, the molten liquid cannot be sprayed, and sometimes the soft magnetic alloy powder cannot be produced. When b is too large, the melting point Tm becomes too low, the proportion of irregular particles in the soft magnetic alloy powder increases, the coercive force increases, and the relative magnetic permeability decreases.
[0116] The P content (c) satisfies 0≤c≤0.200. That is, P may be absent. It is more preferred to satisfy 0≤c≤0.150, and further preferably to satisfy 0.010≤c≤0.050. When c is too large, the melting point Tm of the soft magnetic alloy powder becomes too low, the proportion of irregular particles in the soft magnetic alloy powder increases, the coercive force increases, and the relative magnetic permeability decreases.
[0117] The content (d) of Si satisfies 0≤d≤0.250. That is, Si may be absent. More preferably, 0≤d≤0.200 is satisfied. When d is too large, the melting point Tm of the soft magnetic alloy powder becomes too low, the circularity decreases, the proportion of irregular particles in the soft magnetic alloy powder increases, the coercive force increases, and the relative magnetic permeability decreases.
[0118] The Cr content (e) satisfies 0≤e≤0.030. That is, Cr may be absent. More preferably, 0.001≤e≤0.010 is satisfied. By containing Cr, the corrosion resistance of the soft magnetic alloy powder is easily increased. When e is too large, the proportion of irregular particles in the soft magnetic alloy powder increases, the coercive force increases, and the relative magnetic permeability decreases.
[0119] The S content (f) satisfies 0≤f≤0.010. That is, S may not be contained. The larger f is, the smaller the proportion of irregular particles in the soft magnetic alloy powder is, but when f is too large, the coercive force increases and the relative magnetic permeability decreases.
[0120] In addition, the soft magnetic alloy powder involved in this embodiment satisfies 0.160<b+c+d+e+f≤0.430. It can also satisfy 0.190≤b+c+d+e+f≤0.430. When b+c+d+e+f is too large, a soft magnetic alloy powder with high relative magnetic permeability cannot be obtained.
[0121] Furthermore, the soft magnetic alloy powder involved in the present embodiment satisfies 0.500<1-(a+b+c+d+e+f)<0.840. It can also satisfy 0.550≤1-(a+b+c+d+e+f)≤0.800. When 1-(a+b+c+d+e+f) is too small or too large, a soft magnetic alloy powder with high relative magnetic permeability cannot be obtained.
[0122] In the soft magnetic alloy powder of the present embodiment, a part of Co may be substituted with X1 and / or X2.
[0123] X1 is one or more selected from Fe and Ni. Regarding the content of X1, α=0. That is, X1 may be absent. In addition, when the number of atoms of the total composition is set to 100at%, the number of atoms of X1 is preferably 40at% or less. That is, it is preferred to satisfy 0≤α{1-(a+b+c+d+e+f)}≤0.400. In addition, it is more preferred to satisfy 0≤α{1-(a+b+c+d+e+f)}≤0.100. In addition, compared with the case where Fe is completely absent, when a small amount of Fe is contained, the coercive force is likely to decrease and the relative magnetic permeability is likely to increase. In particular, when the Co / Fe atomic ratio is greater than 5 and less than 20, the coercive force is likely to decrease and the relative magnetic permeability is likely to increase.
[0124] X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C and rare earth elements. The content of X2 may be β=0. That is, X2 may not be contained. In addition, when the number of atoms of the entire composition is 100 at%, the number of atoms of X2 is preferably 5.0 at% or less. That is, it is preferred to satisfy 0≤β{1-(a+b+c+d+e+f+g)}≤0.050.
[0125] The range of the amount of substitution of Co with X1 and / or X2 is less than half of Co in terms of atomic number. That is, 0≤α+β<0.50. It can also be 0≤α+β≤0.40. When α+β is too large, especially when α+β≥0.50, the melting point of the soft magnetic alloy tends to become too high, and the molten liquid cannot be sprayed, and sometimes the soft magnetic alloy powder cannot be produced.
[0126] In addition, even when the melting point of the soft magnetic alloy is high, the melt can be sprayed by increasing the atomization temperature. However, when the atomization temperature is high, the roundness of the soft magnetic alloy powder is likely to decrease, the proportion of irregular particles in the soft magnetic alloy powder is likely to increase, the coercive force is likely to increase, and the relative magnetic permeability is likely to decrease.
[0127] In addition, the value obtained by dividing the content ratio of Co by the content ratio of B (hereinafter sometimes referred to as Co / B) may be greater than 2.000 and less than 5.250, greater than 2.000 and less than 5.000, or greater than 2.340 and less than 4.000. When Co / B is within the above range, the melting point Tm of the soft magnetic alloy powder described later is easily lowered, and the atomization temperature is easily lowered.
[0128] In addition, the soft magnetic alloy powder of this embodiment may contain elements other than the elements contained in the above-mentioned main components as inevitable impurities within a range that does not have a significant effect on properties such as relative magnetic permeability, for example, 0.1% by mass or less relative to 100% by mass of the soft magnetic alloy powder.
[0129] Next, a method for evaluating the particle shape and particle size of the soft magnetic alloy powder of the present embodiment will be described.
[0130] The sphericity of the soft magnetic alloy powder can be evaluated by evaluating the circularity of a figure obtained by projecting the particle shape of the soft magnetic alloy powder.
[0131] In this embodiment, the particle shape is evaluated using Morphologi G3 (Malvern Panalytical). Morphologi G3 is a device that uses air to disperse powder and then projects the shape of each particle for evaluation. The particle shape is evaluated within the range of about 0.5 μm to several mm using an optical microscope or a laser microscope. Specifically, according to Figure 3 , Figure 4 As can be seen from the particle shape measurement results 1 and 2 shown in the figure, multiple particle shapes can be projected and evaluated at once. Figure 3 , Figure 4 Many more particle shapes recorded in the particle shape measurement results 1 and 2 shown in the figure were projected and evaluated at once. Figure 3 It is the projection result of powder particles with good particle shape and high roundness. Figure 4 It is the projection result of powder particles with poor particle shape and low roundness.
[0132] Morphologi G3 can make projections of multiple particles at a time and evaluate them. Compared with the existing evaluation methods such as SEM observation, it can evaluate the shapes of multiple particles in a short time. For example, in the embodiment described below, projections are made for 20,000 particles, the circularity of each particle is automatically calculated, and the average circularity is calculated based on the number of particles. In contrast, in the existing SEM observation, the circularity is calculated for each particle one by one using the SEM image, so it is difficult to evaluate the shapes of multiple particles in a short time.
[0133] When the area of the projection is set to S and the length around the projection is set to L, the circularity of the particle is 2(πS) 1 / 2 The circularity of a circle is 1, and the closer the circularity of a particle is to 1, the higher the sphericity of the particle.
[0134] The soft magnetic alloy powder according to the present embodiment has the above-mentioned composition, and can improve the average circularity, and specifically, can be 0.93 or more. The average circularity is preferably 0.95 or more.
[0135] The proportion of irregular-shaped particles was evaluated by the following method.
[0136] For the 20,000 particles after the circularity measurement, the cumulative number ratio (cumulative number) from the lowest circularity is calculated. The smaller the cumulative number ratio from the lowest circularity to 0.50, the smaller the ratio of irregular-shaped particles.
[0137] The soft magnetic alloy powder involved in this embodiment has the above-mentioned composition, so that the melting point Tm can be within the range of 900°C ≤ Tm ≤ 1200°C, and the proportion of irregular particles can be reduced. In addition, the cumulative number ratio from the lowest circularity to 0.50 can be specifically 2.5% or less or 2.0% or less. The cumulative number ratio from the lowest circularity to 0.50 is preferably 1.5% or less. In addition, the lower limit of the cumulative number ratio from the lowest circularity to 0.50 is not particularly limited. For example, it can be 0.05% or more.
[0138] An example of a graph obtained by taking the circularity as the horizontal axis and the cumulative number ratio as the vertical axis is shown in FIG. Figure 5 and Figure 6 In the case of the solid line, the cumulative number ratio from the minimum circularity to 0.50 is less than 1.5%. In contrast, in the case of the dotted line, the cumulative number ratio from the minimum circularity to 0.50 is greater than 1.5% and less than 2.0%. That is, it can be evaluated that the proportion of irregular particles in the case of the solid line is smaller than that in the case of the dotted line.
[0139] The method for evaluating the particle size is shown below.
[0140] In the present embodiment and the examples described below, the particle size is evaluated on a volume basis. The method for measuring the average particle size (D50) on a volume basis is not particularly limited. For example, a laser diffraction particle size distribution measuring device can be used to obtain the average particle size (D50) on a volume basis.
[0141] In the present embodiment, the average particle size of the soft magnetic metal powder is not particularly limited, and may be, for example, 5 μm or more and 50 μm or less.
[0142] Hereinafter, the glass transition temperature Tg, the melting point Tm, and the like will be described with reference to the drawings.
[0143] exist Figure 7 In FIG. 1 , the solid line is an example of the thermal property measurement results of the soft magnetic alloy powder of the present embodiment using a differential scanning calorimeter (DSC) (hereinafter also referred to as DSC measurement results), and the dotted line is an example of the DSC measurement results of the Fe-based soft magnetic alloy powder containing amorphous. The heating rate is constant. In general, sometimes the temperature at which the soft magnetic alloy starts to melt (at Figure 7 The melting point is Tm1 in the example, and sometimes the temperature at which melting ends (at Figure 7 In the present invention, the temperature at which melting ends (Tm2) is taken as the melting point. Figure 7 This is because the temperature at which melting ends has a greater impact on the atomization temperature and the temperature of the molten metal when implementing the atomization method such as gas atomization described later, and has a greater impact on the characteristics of the soft magnetic alloy powder obtained by the atomization method.
[0144] In addition, when the temperature of the soft magnetic alloy powder of the present embodiment containing amorphous is increased, a glass transition reaction (endothermic reaction) occurs at a specific temperature. This temperature is the glass transition temperature Tg. When the temperature is further increased, a crystallization reaction (exothermic reaction) occurs at a certain temperature. This temperature is the crystallization start temperature Tx. At this time, the supercooled liquid region ΔT is represented by Tx-Tg.
[0145] The supercooled liquid region is related to the stabilization of amorphous phase. The wider the supercooled liquid region is, the larger the ΔT is, and the higher the amorphous phase forming ability is. On the other hand, when the supercooled liquid region is narrow, the amorphous phase forming ability is low. ΔT is preferably 20°C or more.
[0146] exist Figure 8 , Fig. 9In the figure, the solid line is an example of the DSC thermophysical property measurement result of the soft magnetic alloy powder of the present embodiment, and the dotted line is an example of the DSC measurement result of the Fe-based soft magnetic alloy powder containing amorphous. The heating rate is constant. In the soft magnetic alloy powder of the present embodiment, there is a glass transition temperature Tg and a crystallization start temperature Tx. In contrast, the Fe-based soft magnetic alloy powder containing amorphous does not have a glass transition temperature Tg. In addition, the crystallization start temperature of the Fe-based soft magnetic alloy powder containing amorphous is not shown.
[0147] The soft magnetic alloy powder of this embodiment has the characteristics of low Tm and Tg compared with the Fe-based soft magnetic alloy powder containing amorphous. As a result, the atomization temperature can be reduced. In addition, the coercive force of the soft magnetic alloy powder can be reduced, the relative magnetic permeability of the soft magnetic alloy powder itself can be improved, the average circularity of the soft magnetic alloy powder can be improved, and the proportion of irregular particles in the soft magnetic alloy powder can be reduced. In addition, the filling rate of the magnetic core using the soft magnetic alloy powder can be increased, and the relative magnetic permeability can be improved.
[0148] Hereinafter, a method for producing the soft magnetic alloy powder according to the present embodiment will be described.
[0149] As a method for producing the soft magnetic alloy powder of the present embodiment, for example, a gas atomization method can be cited.
[0150] Hereinafter, a method for producing soft magnetic alloy powder by gas atomization will be described.
[0151] The inventors of the present invention have found that using Fig. 10A and Fig. 10B When the atomizing device shown is used as the atomizing device, it is easy to obtain soft magnetic metal powder with good particle shape.
[0152] like Fig. 10A As shown, the atomizing device 10 includes a molten metal supplying portion 20 and a cooling portion 30 disposed vertically below the molten metal supplying portion 20. In the drawings, the vertical direction is a direction along the Z axis.
[0153] The molten metal supply unit 20 has a heat-resistant container 22 for storing the molten metal 21. In the heat-resistant container 22, the raw materials of each metal element weighed in accordance with the composition of the finally obtained soft magnetic alloy powder are melted by the heating coil 24 to form the molten metal 21. The temperature during melting, that is, the temperature of the molten metal 21 can be determined in consideration of the melting point of the raw materials of each metal element and the melting point (Tm) of the molten metal 21, and can be, for example, 1200 to 1600°C.
[0154] The molten metal 21 is discharged from the discharge port 23 to the cooling unit 30 in the form of dripping molten metal 21a. High-pressure gas is sprayed from the gas spray nozzle 26 toward the discharged dripping molten metal 21a, and the dripping molten metal 21a forms a plurality of droplets that move toward the inner surface of the cylinder 32 along the flow of the gas.
[0155] As the gas injected from the gas injection nozzle 26, an inert gas or a reducing gas is preferred. As the inert gas, for example, nitrogen, argon, helium, etc. can be used. As the reducing gas, for example, ammonia decomposition gas, etc. can be used. However, when the molten metal 21 is a metal that is difficult to oxidize, the gas injected from the gas injection nozzle 26 may also be air.
[0156] The dripping molten metal 21a moving toward the inner surface of the cylinder 32 collides with the cooling liquid flow 50 formed into an inverted cone inside the cylinder 32, further splits and refines, and is cooled and solidified to become a solid alloy powder. The axis O of the cylinder 32 is inclined at a predetermined angle θ1 relative to the vertical line Z. The predetermined angle θ1 is not particularly limited, and is preferably 0 to 45 degrees. By becoming such an angle range, it is easy to discharge the dripping molten metal 21a from the discharge port 23 toward the cooling liquid flow 50 formed into an inverted cone inside the cylinder 32.
[0157] A discharge portion 34 is provided at the bottom along the axis O of the cylinder 32, and the alloy powder contained in the coolant flow 50 can be discharged to the outside together with the coolant. The alloy powder discharged together with the coolant is separated from the coolant in an external storage tank, etc. and taken out. There are no particular restrictions on the coolant, and cooling water can be used.
[0158] Therefore, by adjusting the water pressure of the cooling water, the average circularity of the soft magnetic alloy powder finally obtained can be adjusted. The lower the water pressure, the higher the average circularity of the soft magnetic alloy powder finally obtained, but when the water pressure is too low, the cooling water flow 50 formed into an inverted cone cannot be obtained. However, even if the water pressure is changed, the proportion of irregular particles will not change greatly. In addition, there is no particular restriction on the method for adjusting the water pressure. It can be appropriately determined according to the cooling water supply method. For example, when cooling water is supplied by a pump, the water pressure of the cooling water can be adjusted by adjusting the pump pressure.
[0159] In the present embodiment, since the dripping molten metal 21a collides with the coolant flow 50 formed into an inverted cone, the flight time of the droplet of the dripping molten metal 21a is shortened compared to the case where the coolant flow is along the inner surface 33 of the cylinder 32. If the flight time is shortened, the rapid cooling effect is promoted, and the amorphous rate X of the obtained soft magnetic alloy powder increases. In addition, the average circularity is easily increased. In addition, if the flight time is shortened, the droplet of the dripping molten metal 21a is not easily oxidized, so the refinement of the obtained soft magnetic alloy powder is also promoted, and the quality of the soft magnetic alloy powder is also improved.
[0160] In the present embodiment, in order to form the coolant flow in the cylindrical body 32 into an inverted cone shape, the flow of the coolant in the coolant introduction portion (coolant discharge portion) 36 for introducing the coolant into the cylindrical body 32 is controlled. Fig. 10B The structure of the cooling liquid introduction portion 36 is shown.
[0161] like Fig. 10B As shown, the outer portion (outer space portion) 44 located on the radially outer side of the cylinder 32 and the inner portion (inner space portion) 46 located on the radially inner side of the cylinder 32 are defined by the frame 38. The outer portion 44 and the inner portion 46 are separated by the partition 40, and the outer portion 44 and the inner portion 46 are connected by a passage portion 42 formed at the upper portion of the partition 40 in the direction of the axial core O, so that the coolant can flow.
[0162] A single or multiple nozzles 37 are connected to the outer portion 44, and the coolant enters the outer portion 44 from the nozzles 37. In addition, a coolant discharge portion 52 is formed below the inner portion 46 in the axial direction O, and the coolant in the inner portion 46 is discharged (extracted) into the cylinder 32.
[0163] The outer peripheral surface of the frame 38 serves as a flow path inner peripheral surface 38b that guides the flow direction of the coolant in the inner portion 46, and an outer convex portion 38a1 that is continuous from the flow path inner peripheral surface 38b of the frame 38 and protrudes radially outward is formed at the lower end 38a of the frame 38. Therefore, the annular gap between the front end of the outer convex portion 38a1 and the inner surface 33 of the cylinder 32 serves as a coolant discharge portion 52. A flow path deflecting surface 62 is formed on the flow path side upper surface of the outer convex portion 38a1.
[0164] like Fig. 10B As shown, due to the outer convex portion 38a1, the radial width D1 of the coolant discharge portion 52 is narrower than the radial width D2 of the main body of the inner portion 46. Since D1 is narrower than D2, the coolant flowing down the inner peripheral surface 38b of the flow path inside the inner portion 46 toward the lower side of the axis O then flows along the flow path deflection surface 62 of the frame 38, collides with the inner surface 33 of the cylinder 32, and is reflected. As a result, as shown in FIG. Fig. 10AAs shown, the coolant is discharged from the coolant discharge portion 52 into the interior of the cylinder 32 in an inverted cone shape to form a coolant flow 50. When D1=D2, the coolant discharged from the coolant discharge portion 52 forms a coolant flow along the inner surface 33 of the cylinder 32.
[0165] D1 / D2 is preferably 2 / 3 or less, more preferably 1 / 2 or less, and most preferably 1 / 10 or more.
[0166] The coolant flow 50 flowing out of the coolant discharge portion 52 is an inverted conical flow that advances straight from the coolant discharge portion 52 toward the axis O, but may also be a spiral inverted conical flow.
[0167] The gas injection temperature, gas injection pressure, etc. may be appropriately set according to the target soft magnetic alloy powder particle size. The gas injection temperature may be, for example, room temperature or higher and 200° C. or lower. The gas injection pressure may be, for example, 0.5 MPa or higher and 19 MPa or lower.
[0168] The soft magnetic alloy powder according to the present embodiment can be obtained by the above method. In order to appropriately control the particle shape and particle size, the soft magnetic alloy powder preferably contains amorphous materials and does not contain crystals (nanocrystals).
[0169] It is preferred to heat treat the amorphous soft magnetic alloy powder obtained by the gas atomization method. For example, by heat treating at 350 to 575°C for 0.1 to 2 hours, it is possible to prevent the powders from sintering to each other and causing the powders to coarsen, and to promote the diffusion of elements, so that the thermodynamic equilibrium state can be reached in a short time, and deformation and stress can be removed. In addition, nanocrystals can also be precipitated at this time.
[0170] The use of the soft magnetic alloy powder involved in this embodiment is not particularly limited, and is suitable for use in applications requiring high relative magnetic permeability. For example, a magnetic core can be cited. It is particularly suitable for use as a magnetic core for a power inductor. In addition, it is also suitable for use in magnetic components using soft magnetic alloy powder, such as thin film inductors and magnetic heads. In addition, the magnetic core and magnetic components using the soft magnetic alloy powder can be applied to electronic devices.
[0171] In addition, the smaller the average particle size of the soft magnetic alloy powder, the lower the high-frequency loss. Therefore, soft magnetic alloy powders with a small average particle size are particularly suitable for high-frequency components. In addition, the larger the average particle size of the soft magnetic alloy powder, the easier it is to improve the magnetic permeability of the magnetic core. Therefore, soft magnetic alloy powders with a large average particle size are suitable for components that require high magnetic permeability.
[0172] (Second Embodiment)
[0173] Hereinafter, a second embodiment will be described, and matters not particularly described are the same as those of the first embodiment.
[0174] The soft magnetic alloy powder of this embodiment has a composition formula (Co (1-(α+β)) X1 α X3 β ) (1-(a+b+c+d+e)) M a B b P c Si d Cr e (atomic ratio) of the main components of the soft magnetic alloy powder,
[0175] X1 is one or more selected from Fe and Ni,
[0176] X3 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C, S and rare earth elements,
[0177] M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V,
[0178] 0<a≤0.140,
[0179] 0.160<b≤0.250,
[0180] 0≤c≤0.200,
[0181] 0≤d≤0.250,
[0182] 0≤e≤0.030,
[0183] 0.160<b+c+d+e≤0.430,
[0184] 0.500<1-(a+b+c+d+e)<0.840,
[0185] α ≥ 0,
[0186] β ≥ 0,
[0187] 0≤α+β<0.50,
[0188] A pressure X is applied to the soft magnetic alloy powder. P The coercivity at H , we will use the least squares method to find X P With Y H The straight line obtained by linear approximation of the relationship is represented by Y H =kX P When +l, k (unit: Oe / MPa) is 0≤k≤0.00100.
[0189] Generally speaking, there is a tendency that the coercive force of a soft magnetic alloy powder having a composition containing more Co is lower than that of a soft magnetic alloy powder having a composition containing more Fe.
[0190] In addition, the magnetic core can be made by molding the soft magnetic alloy powder. Furthermore, the higher the pressure during molding, the higher the density of the soft magnetic alloy powder can be filled. By filling the soft magnetic alloy powder at a high density, the relative magnetic permeability of the magnetic core can be improved.
[0191] However, when the soft magnetic alloy powder is molded to make a magnetic core, when the pressure during molding is high and the soft magnetic alloy powder is filled at a high density, the magnetic body (soft magnetic alloy powder) will deform inside, so there is a tendency for the coercive force of the magnetic core to increase and the relative magnetic permeability to decrease.
[0192] The soft magnetic alloy powder according to the present embodiment has the above-mentioned composition, and the change in coercive force when the soft magnetic alloy powder is pressurized is small. P The coercivity at H , we will use the least squares method to find X P With Y H The straight line obtained by linear approximation of the relationship is represented by Y H =kX P When +1, k (unit: Oe / MPa) is 0≤k≤0.00100. Alternatively, it may be 0.00015≤k≤0.00095.
[0193] When k is outside the above range, the higher the pressure during molding, the smaller the ratio of the increase in the relative magnetic permeability of the magnetic core relative to the increase in pressure. In contrast, when k is within the above range, the ratio of the increase in the relative magnetic permeability of the magnetic core relative to the increase in pressure is not easy to become smaller than when k is outside the above range. That is, when comparing the case of using a soft magnetic alloy powder with k within the above range with the case of using a soft magnetic alloy powder with k outside the above range, the higher the pressure during molding, the greater the difference in the relative magnetic permeability of the obtained magnetic core.
[0194] Hereinafter, each component of the soft magnetic alloy powder according to the present embodiment will be described in detail.
[0195] The content (a) of M satisfies 0<a≤0.140. It may also satisfy 0.001≤a≤0.140. In addition, it may satisfy 0.003≤a≤0.100, it may satisfy 0.003≤a≤0.040, and it may also satisfy 0.020≤a≤0.040. When M is not contained, the coercive force of the soft magnetic alloy powder becomes too high and the relative magnetic permeability of the magnetic core decreases. When a is too large, k becomes too large. Furthermore, when the pressure during molding of the soft magnetic alloy powder is high, when the filling rate of the magnetic core is the same, the relative magnetic permeability of the magnetic core decreases compared to the case where a is within the above range and k is small.
[0196] The B content (b) satisfies 0.160<b≤0.250. It may also satisfy 0.180≤b≤0.250, and it may also satisfy 0.180≤b≤0.220. When b is too small or too large, k becomes too high. Furthermore, when the pressure during molding of the soft magnetic alloy powder is high, when the filling rate of the magnetic core is the same, the relative magnetic permeability of the magnetic core decreases compared to the case where b is within the above range and k is small.
[0197] The P content (c) satisfies 0≤c≤0.200. That is, P may be absent. It may satisfy 0≤c≤0.150, 0≤c≤0.050, or 0≤c≤0.010. When c is too large, k increases. Furthermore, when the pressure during molding of the soft magnetic alloy powder is high, when the filling rate of the magnetic core is the same, the relative magnetic permeability of the magnetic core decreases compared to the case where c is within the above range and k is small.
[0198] The Si content (d) satisfies 0≤d≤0.250. That is, Si may be absent. It may satisfy 0≤d≤0.200, 0≤d≤0.100, or 0.050≤d≤0.070. When d is too large, k becomes too high. Furthermore, when the pressure during molding of the soft magnetic alloy powder is high, when the filling rate of the magnetic core is the same, the relative magnetic permeability of the magnetic core decreases compared to the case where d is within the above range and k is small.
[0199] The Cr content (e) satisfies 0≤e≤0.030. That is, Cr may be absent. It may satisfy 0≤e≤0.020, 0≤e≤0.010, or 0≤e≤0.001. When e is too large, k becomes too high. Furthermore, when the pressure during molding of the soft magnetic alloy powder is high, when the filling rate of the magnetic core is the same, the relative magnetic permeability of the magnetic core decreases compared to the case where e is within the above range and k is small.
[0200] In addition, the soft magnetic alloy powder involved in this embodiment satisfies 0.160<b+c+d+e≤0.430. It can satisfy 0.180≤b+c+d+e≤0.430, and it can also satisfy 0.180≤b+c+d+e≤0.400. When b+c+d+e is too large, k becomes too high. And, when the pressure when the soft magnetic alloy powder is molded is high, when the filling rate of the magnetic core is the same, the relative magnetic permeability of the magnetic core decreases compared with the case where b+c+d+e is within the above range and k is small.
[0201] Furthermore, the soft magnetic alloy powder involved in the present embodiment satisfies 0.500<1-(a+b+c+d+e)<0.840. It can satisfy 0.550≤1-(a+b+c+d+e)≤0.800, and it can also satisfy 0.580≤1-(a+b+c+d+e)≤0.800. When 1-(a+b+c+d+e) is too small, there is a tendency for the saturation magnetic flux density to be low. When 1-(a+b+c+d+e) is too large, there is a tendency for the coercive force to be high.
[0202] In the soft magnetic alloy powder of the present embodiment, a part of Co may be substituted with X1 and / or X3.
[0203] X1 is one or more selected from Fe and Ni. Regarding the content of X1, α=0 may be sufficient. That is, X1 may not be contained. In addition, when the number of atoms of the total composition is set to 100 at%, the number of atoms of X1 may be 40 at% or less. That is, 0≤α{1-(a+b+c+d+e)}≤0.400 may be satisfied. In addition, 0≤α{1-(a+b+c+d+e)}≤0.360 may also be satisfied, and 0≤α{1-(a+b+c+d+e)}≤0.144 may also be satisfied. In addition, compared with the case where Fe is completely absent, when a small amount of Fe is contained, the coercive force is more likely to decrease, and the relative magnetic permeability is more likely to increase. In particular, when the Co / Fe atomic ratio is greater than 5 and less than 20, the coercive force is more likely to decrease, and the relative magnetic permeability is more likely to increase.
[0204] X3 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C, S and rare earth elements. X3 may also be one or more selected from Al, Zn, Sn, Cu, Bi, La, Y, N, O, C and S. Regarding the content of X3, β=0 may be sufficient. That is, X3 may not be contained. In addition, when the number of atoms constituting the whole is set to 100 at%, the number of atoms of X3 may be 5.0 at% or less. That is, 0≤β{1-(a+b+c+d+e)}≤0.050 may be satisfied.
[0205] The range of the amount of substitution of Co with X1 and / or X3 is 0≤α+β<0.50. When α+β>0.50, k becomes too high. In addition, when the pressure during the molding of the soft magnetic alloy powder is high, the relative magnetic permeability of the magnetic core decreases when the filling rate of the magnetic core is the same, compared with the case where 0≤α+β<0.50 is satisfied and k is small. Alternatively, 0≤α+β≤0.50 may be used.
[0206] In addition, the soft magnetic alloy powder of this embodiment may contain elements other than the elements contained in the above-mentioned main components as inevitable impurities within a range that does not significantly affect the properties such as relative magnetic permeability, for example, 0.1% by mass or less relative to 100% by mass of the soft magnetic alloy powder.
[0207] Hereinafter, a method for measuring k of the soft magnetic alloy powder of the present embodiment will be described. First, a method for producing a pressurized soft magnetic alloy powder will be described.
[0208] 2 g of the soft magnetic alloy powder of this embodiment is weighed. Too much or too little powder may lead to inaccurate results.
[0209] Next, pour the weighed powder into a Φ8mm mold. A mold with a diameter that is too large or too small may cause inaccurate results.
[0210] Next, use a manual press to press the powder poured into the mold at a specific pressure. P Apply pressure for 30 seconds.
[0211] Next, the pressurized powder is taken out from the mold to obtain pressurized powder.
[0212] When measuring k, the pressure X when preparing for pressurization P The three powders are powder with a pressure of 400 MPa, powder with a pressure of 800 MPa, and unpressurized powder. P Then, the coercivity (unit: Oe) of each powder was measured. Then, the applied pressure X P The coercivity at H , we will use the least squares method to find X P With Y H The straight line obtained by linear approximation of the relationship is represented by Y H =kX P + l, calculate the slope k of the approximate straight line (unit: Oe / MPa). p Even when the pressure is set to 400 MPa or 800 MPa for 30 seconds, the soft magnetic alloy powder of the present embodiment does not consolidate.
[0213] In the present embodiment, the average particle size of the soft magnetic metal powder is not particularly limited, and may be, for example, 5 μm or more and 50 μm or less.
[0214] The method for producing the soft magnetic alloy powder by the gas atomization method is the same as that of the first embodiment. In order to appropriately control k, it is preferable that the soft magnetic alloy powder contains amorphous materials but does not contain crystals (nanocrystals).
[0215] The soft magnetic alloy powder containing amorphous obtained by the gas atomization method can be heat treated. When heat treated, for example, by heat treating at 250-600°C, preferably 250-550°C, and more preferably 250-450°C for 0.1-2 hours, it is possible to prevent the powders from sintering to each other and causing the powders to coarsen, and to promote the diffusion of elements, reach a thermodynamic equilibrium state in a short time, and remove deformation and stress. In addition, crystallization can proceed due to heat treatment, but it is preferred to heat treat at a low temperature to the extent that crystals with a grain size exceeding 100nm are not precipitated. In addition, by heat treating at an appropriate temperature and time, k can be reduced, and the relative magnetic permeability of the magnetic core when the pressure during molding is high can be particularly improved. In addition, nanocrystals can be precipitated at this time. However, when the heat treatment temperature is too high or when the heat treatment time is too long, k becomes too high. Furthermore, when the pressure during the molding of the soft magnetic alloy powder is high, the relative magnetic permeability of the core decreases when the filling rate of the core is the same, compared with the case where the heat treatment temperature and heat treatment time are appropriate and k is small.
[0216] The use of the soft magnetic alloy powder involved in this embodiment is not particularly limited, and is suitable for use in applications requiring high relative magnetic permeability. For example, a magnetic core can be cited. It is particularly suitable for use as a magnetic core for power inductors. In addition, it can also be suitable for magnetic components using soft magnetic alloy powder, such as thin film inductors and magnetic heads. In addition, the magnetic core and magnetic components using the soft magnetic alloy powder are suitable for use in electronic devices.
[0217] [Example]
[0218] Hereinafter, the present invention will be specifically described based on examples.
[0219] (Experimental Example 1)
[0220] Ingots of various materials were prepared and weighed so as to obtain master alloys having the compositions shown in Table 1. Then, the ingots were placed in a crucible disposed in a gas atomizer.
[0221] Next, the master alloy is stored in a heat-resistant container 22 disposed in the atomizing device 10. Next, after the cylinder 32 is evacuated, the heat-resistant container 22 is heated by high-frequency induction using a heating coil 24 disposed outside the heat-resistant container 22, so that the raw metals in the heat-resistant container 22 are melted and mixed, thereby obtaining a molten metal (molten liquid).
[0222] The obtained molten liquid was sprayed into the cylinder 32 of the cooling unit 30 at the atomization temperature described in Table 1, and argon gas was sprayed at a spray gas pressure of 7 MPa, thereby forming a plurality of molten droplets. The molten droplets collided with the inverted cone-shaped cooling water flow formed by cooling water supplied at a pump pressure of 10 MPa to form fine powder, which was then recovered. Among them, the atomization temperature of Sample No. 3 and 4 in Table 1 was too low, and the molten liquid could not be sprayed.
[0223] Among them, Fig. 10A , Fig. 10B In the atomizing device 10 shown, the inner diameter of the inner surface of the cylinder 32 is 300 mm, D1 / D2 is 1 / 2, and the angle θ1 is 20 degrees.
[0224] In Experimental Example 1, heat treatment was performed at 475° C. for 60 minutes. In addition, ICP analysis confirmed that the composition of the mother alloy was substantially the same as the composition of the soft magnetic alloy powder.
[0225] Confirm whether each soft magnetic alloy powder obtained contains amorphous and nanocrystals. Calculate the amorphization degree X using XRD. Soft magnetic metal powders with X of 85% or more are recorded as amorphous in the microstructure. For the case where the amorphization rate is less than 85%, confirm whether it contains crystals larger than nanocrystals by evaluating the crystallite size using the Scherrer formula of XRD. When it does not contain crystals larger than nanocrystals, it is recorded as amorphous + nanocrystals; when it contains crystals larger than nanocrystals, it is recorded as crystals. The results are shown in Table 1.
[0226] The shapes of the powder particles of each soft magnetic alloy powder obtained were evaluated. Specifically, the circularity of 20,000 particles was measured, and the average circularity based on the number and the cumulative number ratio from the lowest circularity to 0.50 were calculated. The results are shown in Table 1. In addition, for each embodiment and comparative example, when the cumulative number ratio is less than 2.0%, there are few irregular particles; when the cumulative number ratio is less than 1.5%, there are particularly few irregular particles. In addition, for each embodiment and comparative example, the average particle size (D50) based on the volume basis was confirmed to be approximately 25μm using a laser diffraction particle size distribution measuring device (HELOS&RODOS (Sympatec)).
[0227] Each of the obtained soft magnetic alloy powders was subjected to DSC measurement using STA449F3 (NETZSCH) to confirm the presence or absence of Tg. In addition, Tm and ΔT were measured. The results are shown in Table 1.
[0228] The coercive force Hc of each soft magnetic alloy powder obtained was measured using K-HC1000 (Tohoku Special Steel Co., Ltd.). The results are shown in Table 1. Hc is not particularly limited. Hc may be 0.50 Oe or less. Hc is preferably 0.20 Oe or less.
[0229] Next, a toroidal magnetic core was made from each soft magnetic alloy powder. Specifically, a phenolic resin as an insulating binder was mixed into each soft magnetic alloy powder to make the phenolic resin amount reach 3% by mass of the total amount, and a general planetary mixer was used as a mixer to granulate to obtain a granulated powder of about 500 μm. Next, the powder was granulated at a surface pressure of 4 ton / cm 2 (392MPa) The obtained granulated powder is molded to make the shape inner diameter The obtained molded body was cured at 150°C to produce a toroidal core.
[0230] Then, a UEW wire was wound around the toroidal core, and μ (relative magnetic permeability) was measured at 100 kHz using a 4284A PRECISION LCR METER (Hewlett-Packard Company). The results are shown in Table 1. Among them, the case where the relative magnetic permeability μ was 30 or more was evaluated as good.
[0231]
Table 1
[0232]
[0233] According to Table 1, as samples No. 1 to 4 and 1a containing amorphous Fe-based soft magnetic alloys, the atomization temperature required for spraying is as high as 1500°C or more due to the high Tm. That is, the range of atomization temperatures that can produce soft magnetic alloy powders is narrow. In addition, the obtained soft magnetic alloy powder does not have Tg. Therefore, the coercive force of the soft magnetic alloy powder increases, the circularity decreases, and there are many irregular particles. Furthermore, the relative permeability μ of the annular magnetic core made using the soft magnetic alloy powder decreases.
[0234] In contrast, as samples No. 5 to 8 and 5a, which contain a lot of Co, the atomization temperature required for spraying is low due to the low Tm, and spraying can be performed at an atomization temperature of 1300°C. That is, the range of atomization temperatures that can produce soft magnetic alloy powders is wide. In addition, the obtained soft magnetic alloy powder has Tg. Therefore, the coercive force of the soft magnetic alloy powder is reduced, the circularity is increased, and the number of irregular particles is small. Furthermore, the relative permeability μ of the annular magnetic core made using the soft magnetic alloy powder is increased.
[0235] (Experimental Example 2)
[0236] In Experimental Example 2, except that the pump pressure for supplying cooling water was changed from that of Sample No. 1, soft magnetic alloy powders and toroidal cores of Samples Nos. 9 and 10 were produced under the conditions described in Experimental Example 1. The results are shown in Table 2.
[0237]
Table 2
[0238]
[0239] According to Table 2, by reducing the pump pressure, the average roundness of the particles of the soft magnetic alloy powder is improved. However, the change in the cumulative number ratio is small, and the change in the proportion of irregular particles is also small. Since Samples No. 9 and 10 are Fe-based soft magnetic alloys containing amorphous, Tm is high. In addition, the obtained soft magnetic alloy powder does not have Tg. Therefore, the coercive force of the soft magnetic alloy powder increases, and there are many irregular particles. Furthermore, the relative permeability μ of the annular core made using the soft magnetic alloy powder is reduced.
[0240] (Experimental Example 3)
[0241] In Experimental Example 3, soft magnetic alloy powders and toroidal cores of Sample Nos. 9 to 16 were prepared under the conditions described in Experimental Example 1 except that a portion of Co in Sample No. 8 was replaced with Fe.
[0242] In addition, soft magnetic alloy powders and toroidal cores of Sample Nos. 8a to 8e were produced under the same conditions as Sample No. 8 except that the composition was changed. The results are shown in Table 3A.
[0243]
Table 3
[0244]
[0245]
Table 3A
[0246]
[0247] According to Table 3, the particle shape of samples No. 11 to 14 having a composition within the specified range is good, and the relative magnetic permeability μ of the toroidal core is good. According to samples No. 11 to 14, there is a tendency that the more the Fe content increases, the higher the Tm, the higher the coercive force, and the lower the relative magnetic permeability μ. Moreover, in sample No. 16 where α+β>0.500 and the Co content ratio is too small, the melting point of the soft magnetic alloy becomes too high, and the molten liquid cannot be sprayed at an atomization temperature of 1300°C. However, compared with samples No. 8 and 12 outside the above range, sample No. 11 having a Co / Fe atomic ratio of 5 or more and 20 or less has a lower coercive force and an increased relative magnetic permeability μ.
[0248] According to Table 3A, for each sample having a composition within a specified range, having Tg and Tm within a specified range, the atomization temperature required for spraying is low, and spraying can be performed at an atomization temperature of 1300°C. That is, the range of atomization temperatures that can produce soft magnetic alloy powders is wide. In addition, the obtained soft magnetic alloy powder has Tg. Therefore, the coercive force of the soft magnetic alloy powder is reduced, the circularity is increased, and the number of irregular particles is small. Furthermore, the relative magnetic permeability μ of the annular magnetic core made using the soft magnetic alloy powder is increased. In addition, when Co / B is higher than sample No. 8, there is a tendency that the higher the Co / B, the higher the Tm, the smaller the average circularity, the greater the coercive force, and the lower the relative magnetic permeability μ.
[0249] (Experimental Example 4)
[0250] In Experimental Example 4, soft magnetic alloy powder and toroidal cores were prepared under the same conditions as in Experimental Example 3 and Sample No. 11 except that the contents of the elements contained in the main component were changed. The results are shown in Tables 4 to 7.
[0251]
Table 4
[0252]
[0253]
Table 5
[0254]
[0255]
Table 6
[0256]
[0257]
Table 7
[0258]
[0259] Table 4 shows experimental examples in which the contents of Co, Fe, and M (Nb) were changed. Samples No. 18 to 22 having compositions within the specified range have Tg and Tm within the specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative permeability of the toroidal core is increased.
[0260] In contrast, Sample No. 17, which does not contain M (Nb), does not have Tg. As a result, the average circularity of the soft magnetic alloy powder is low, there are many irregular particles, and the coercive force is increased. In addition, the relative magnetic permeability of the toroidal core is increased. In addition, the Tm of Sample No. 23, which has an excessive M content, becomes too low. As a result, the average circularity of the soft magnetic alloy powder is low, there are many irregular particles, and the coercive force is increased. In addition, the relative magnetic permeability of the toroidal core is increased.
[0261] In Table 5, Samples No. 24 to 27 are experimental examples in which the contents of Co, Fe, and B were changed from Sample No. 11 (b). Samples No. 25 and 26, which have compositions within the specified range, have Tg and Tm within the specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core increases. In contrast, the melting point of the soft magnetic alloy of Sample No. 24, which has too little B content, becomes too high, and the molten liquid cannot be sprayed at an atomization temperature of 1300°C. The Tm of Sample No. 27, which has too much B content, becomes too low. As a result, the soft magnetic alloy powder has many irregular particles and the coercive force increases. In addition, the relative magnetic permeability of the toroidal core decreases.
[0262] In Table 5, Sample No. 28 to 34 are experimental examples in which the contents of Co, Fe and P (c) are changed from Sample No. 11. Sample No. 28 to 33 having a composition within the specified range have Tg and have a Tm within the specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core increases. In contrast, the Tm of Sample No. 34 having an excessive P content becomes too low. As a result, the average circularity of the soft magnetic alloy powder is low, the number of irregular particles is large, and the coercive force is increased. In addition, the relative magnetic permeability of the toroidal core is reduced.
[0263] In Table 5, Samples No. 35 to 41 are experimental examples in which the contents (d) of Co, Fe, and Si are changed from Sample No. 11. Samples No. 35 to 40 having compositions within the prescribed range have Tg and Tm within the prescribed range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core increases. In contrast, the Tm of Sample No. 41 having an excessive Si content becomes too low. As a result, the average circularity of the soft magnetic alloy powder is low, the number of irregular particles is large, and the coercive force is increased. In addition, the relative magnetic permeability of the toroidal core decreases.
[0264] In Table 6, Samples No. 42 to 46 are experimental examples in which the contents (e) of Co, Fe, and Cr are mainly changed from Sample No. 11. Samples No. 42 to 45 having compositions within the prescribed range have Tg and Tm within the prescribed range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core is increased. In contrast, the soft magnetic alloy powder of Sample No. 46 having an excessive Cr content has many irregular particles and an increased coercive force. In addition, the relative magnetic permeability of the toroidal core is reduced.
[0265] In Table 7, Samples No. 47 to 49 are experimental examples in which the contents (f) of Co, Fe, and S are mainly changed from Sample No. 11. Samples No. 47 and 48 having compositions within the prescribed range have Tg and Tm within the prescribed range. In addition, the average circularity of the soft magnetic alloy powder is high and there are few irregular particles. In contrast, the coercive force of the soft magnetic alloy powder of Sample No. 49 having an excessive S content is increased. In addition, the relative magnetic permeability of the toroidal core is reduced.
[0266] (Experimental Example 5)
[0267] In Experimental Example 5, a soft magnetic alloy powder and a toroidal core were prepared under the conditions described in Experimental Example 1 except that a portion of Co in Sample No. 8 was replaced with X1 and / or X2. The results are shown in Tables 8 and 9.
[0268]
Table 8
[0269]
[0270]
Table 9
[0271]
[0272] Even if part of Co is replaced by X1 and / or X2, each sample having a composition within the specified range has Tg and has a Tm within the specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core is increased.
[0273] (Experimental Example 6)
[0274] In Experimental Example 6, soft magnetic alloy powder and annular cores were produced under the same conditions as those described in Experimental Example 1 except that the type of M was changed with respect to Sample No. 8. The results are shown in Table 10.
[0275]
Table 10
[0276]
[0277] Even if the type of M is changed, each sample having a composition within the specified range has Tg and a Tm within the specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core is increased.
[0278] (Experimental Example 7)
[0279] In Experimental Example 7, the heat treatment conditions were changed for Sample No. 8, and otherwise, soft magnetic alloy powder and annular magnetic core were produced under the conditions described in Experimental Example 1. Specifically, no heat treatment was performed in Sample No. 109. The heat treatment temperature was increased to 575° C. in Sample No. 110. The results are shown in Table 11. Although not described in Table 11, each sample has a Tg and a Tm within a specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced.
[0280]
Table 11
[0281]
[0282] The soft magnetic alloy powder of sample No. 109 can be said to be the soft magnetic alloy powder before heat treatment in the manufacturing process of the soft magnetic alloy powder of sample No. 8. If the comparison is made before and after the heat treatment at 475°C, it can be considered that since no crystals are generated during the heat treatment, deformation and stress can be removed, so the relative magnetic permeability μ increases.
[0283] Since the soft magnetic alloy powder of Sample No. 110 was heat-treated at 575° C., nanocrystals were generated.
[0284] (Experimental Example 8)
[0285] In Experimental Example 8, except that the average particle size based on volume was changed from that of Sample No. 11, soft magnetic alloy powders and toroidal cores of Samples Nos. 111 and 112 were produced under the conditions described in Experimental Example 3. In addition, except that the B content (b) was reduced and the atomization temperature was 1600° C., soft magnetic alloy powders and toroidal cores of Samples Nos. 113 to 115 were produced under the same conditions as those of Samples Nos. 11, 111, and 112. The results are shown in Table 12.
[0286]
Table 12
[0287]
[0288] According to Table 12, the larger the average particle size, the higher the relative magnetic permeability of the toroidal core. In addition, each of the samples No. 11, 111, and 112 having a composition within the specified range has Tg and has a Tm within the specified range. In addition, the average circularity of the soft magnetic alloy powder is high, the number of irregular particles is small, and the coercive force is reduced. In addition, the relative magnetic permeability of the toroidal core is increased.
[0289] In contrast, each of the samples No. 113 to 115 having too low a B content (b) has no Tg and too high a Tm. As a result, the average circularity of the soft magnetic alloy powder is low, there are many irregular particles, and the coercive force is increased. In addition, the relative magnetic permeability of the toroidal core is reduced.
[0290] (Experimental Example 9)
[0291] To get Co 0.720 Nb 0.020 B 0.180 P 0.010 Si 0.070 Ingots of various materials are prepared and weighed in the manner of master alloys. Then, they are placed in a crucible disposed in a gas atomization device.
[0292] Next, the master alloy is stored in a heat-resistant container 22 disposed in the atomizing device 10. Next, after the cylinder 32 is evacuated, the heat-resistant container 22 is heated by high-frequency induction using a heating coil 24 disposed outside the heat-resistant container 22, so that the raw metals in the heat-resistant container 22 are melted and mixed, thereby obtaining a molten metal (molten liquid).
[0293] The obtained molten liquid was sprayed into the cylinder 32 of the cooling part 30 at an atomization temperature of 1500°C, and argon gas was sprayed at a spray gas pressure of 7 MPa, thereby forming a plurality of droplets. The droplets collided with an inverted cone-shaped cooling water flow formed by cooling water supplied at a pump pressure of 10 MPa, forming fine powder, which was then recovered.
[0294] Among them, Fig. 10A , Fig. 10B In the atomizing device 10 shown, the inner diameter of the inner surface of the cylinder 32 is 300 mm, and the angle θ1 is 20 degrees. In Experimental Example 9, D1 / D2 was set to the conditions shown in Table 13.
[0295] ICP analysis confirmed that the composition of the master alloy was substantially consistent with the composition of the soft magnetic alloy powder.
[0296] Confirm whether each soft magnetic alloy powder obtained has a structure containing amorphous, a structure containing nanocrystals, or a structure containing crystals. XRD is used to confirm whether there is a peak caused by nanocrystals. When the amorphization rate is 85% or more, it is recorded as having a structure containing amorphous; when it is less than 85%, it is recorded as having a structure containing nanocrystals or a structure containing crystals. In addition, when the amorphization rate is 85% or more, TEM is used to confirm whether the structure containing amorphous is a structure containing only amorphous or a structure containing heterogeneous amorphous. According to the results confirmed by TEM, the structure containing only amorphous is recorded as amorphous, and the structure containing heterogeneous amorphous is recorded as heterogeneous amorphous. In addition, for the case where the amorphization rate is less than 85%, it is confirmed whether it contains crystals larger than nanocrystals by evaluating the crystallite size using the Scherrer formula of XRD. When crystals larger than nanocrystals are not contained, it is recorded as having a structure containing nanocrystals. In addition, when there is a structure containing nanocrystals, it is recorded as nanocrystals; when crystals larger than nanocrystals are contained, it is recorded as crystals. The results are shown in Table 13 under the heading "Microstructure".
[0297] Next, weigh 2 g of the obtained soft magnetic alloy powder. Next, pour the weighed powder into a Φ8 mm mold. Next, use a manual press to press the powder poured into the mold with a pressure of X. P The pressurization was performed for 30 seconds. Then, the pressurized powder was taken out from the mold to obtain a pressurized powder.
[0298] When measuring k, unpressurized powder (X P =0), pressure when pressurized X P The powder is 400 MPa and the pressure during pressurization is X P The coercive force (unit: Oe) of each of the three powders was measured using a HC meter (K-HC1000 type (Tohoku Special Steel Co., Ltd.)). P The coercivity at H , we will use the least squares method to find X P With Y H The straight line obtained by linear approximation of the relationship is represented by Y H =kX P+ 1, and the slope k of the approximate straight line was measured. The results are shown in Table 13.
[0299] Next, a toroidal core is made from each soft magnetic alloy powder. Specifically, a phenolic resin as an insulating binder is mixed into each soft magnetic alloy powder to make the phenolic resin amount reach 3% by mass of the total amount, and a general planetary mixer is used as a mixer to granulate to obtain a granulated powder of about 500 μm. Next, the powder is granulated at a surface pressure of 6 ton / cm2 in such a way that the filling rate of the magnetic body reaches 70% to 72%. 2 (588MPa)~Surface pressure 8ton / cm 2 (784MPa) The obtained granulated powder is molded to make the shape inner diameter The obtained molded body was cured at 150°C to produce a toroidal core.
[0300] Then, the coercive force of the toroidal core was measured using an Hc meter (K-HC1000 model (Tohoku Special Steel Co., Ltd.)). A coercive force of 1.00 Oe or less was evaluated as good, 0.50 Oe or less was evaluated as better, and 0.30 Oe or less was evaluated as particularly good.
[0301] Then, UEW wire was wound around the toroidal core, and μ (relative magnetic permeability) was measured at 100 kHz using 4284A PRECISION LCR METER (Hewlett-Packard Company). The results are shown in Table 13. Among them, the case where the relative magnetic permeability μ was 30 or more was evaluated as good, and the case where it was 35 or more was evaluated as particularly good.
[0302]
Table 13
[0303]
[0304] According to Table 13, the core coercivity and relative permeability of samples No. 201 to 203, where k satisfies 0≤k≤0.00100, are good. In contrast, sample No. 204, where D1 / D2 is 1, has too large k, resulting in too high core coercivity and too low core relative permeability.
[0305] (Experimental Example 10)
[0306] In Experimental Example 10, soft magnetic alloy powder and toroidal cores were prepared under the same conditions as those of Sample No. 201 or Sample No. 204 except that Sample No. 201 or Sample No. 204 was heat treated for 60 minutes at the temperature shown in Table 14. The results are shown in Table 14.
[0307]
Table 14
[0308]
[0309] According to Table 14, the coercive force and relative magnetic permeability of the core of samples No. 201, 205 to 209, in which k satisfies 0≤k≤0.00100, are good. In particular, the coercive force and relative magnetic permeability of the core of samples No. 201, 205 to 208, in which the microstructure is a structure having only amorphous materials, a structure including heterogeneous amorphous materials, or a structure including nanocrystals, are better than those of sample No. 209, in which the microstructure is a structure including crystals larger than nanocrystals. In addition, the coercive force and relative magnetic permeability of the core of samples No. 201, 205 to 207, in which the microstructure is a structure having only amorphous materials or a structure including heterogeneous amorphous materials, are better than those of sample No. 208, in which the microstructure is a structure including nanocrystals. In contrast, k of sample No. 210 becomes too large, resulting in excessively high coercive force and excessively low relative magnetic permeability of the core. In addition, in Sample No. 204 and Samples Nos. 211 to 216 obtained by heat-treating Sample No. 204, k became too large regardless of the fine structure, resulting in that the coercive force of the core was too high and the relative magnetic permeability of the core was too low.
[0310] (Experimental Example 11)
[0311] In Experimental Example 11, a part or all of Co was replaced by Fe in Sample No. 207, and the soft magnetic alloy powder and the toroidal magnetic core were prepared under the same conditions as Sample No. 207. The results are shown in Table 15. Among them, regarding the fine structure of the soft magnetic metal powder, only the amorphization rate was confirmed to be 85% or more by XRD. That is, it was confirmed that there was a structure containing amorphous, but it was not confirmed whether the structure containing amorphous was a structure containing only amorphous or a structure containing heterogeneous amorphous.
[0312]
Table 15
[0313]
[0314] According to Table 15, the relative magnetic permeability of the magnetic core of samples No. 207, 217 to 220, in which α+β is within a specific range and satisfies 0≤k≤0.00100, is good. In contrast, the coercive force of the magnetic core of samples No. 222 and 223, in which α+β is too large and k is too large, is too high, resulting in too low relative magnetic permeability of the magnetic core. In addition, in particular, sample No. 217, in which the Co / Fe atomic ratio is greater than 5 and less than 20, has a smaller k, a lower coercive force of the magnetic core, and an increased relative magnetic permeability of the magnetic core, compared with samples No. 207, 218 to 220 in which Co / Fe is outside the above range. Among them, all samples in Table 15 have a structure containing amorphous.
[0315] (Experimental Example 12)
[0316] In Experimental Example 12, the soft magnetic alloy powder and the toroidal core were prepared under the same conditions as those of Sample No. 217 except that the Nb content (a) was changed from Sample No. 217 and the Co and Fe contents were changed. The results are shown in Table 16. In addition, regarding the fine structure of the soft magnetic metal powder, it was not confirmed whether the structure including amorphous substances had only amorphous substances or had a structure including heterogeneous amorphous substances.
[0317]
Table 16
[0318]
[0319] According to Table 16, the coercive force and relative magnetic permeability of the core of samples No. 217, 225 to 229 that satisfy 0.001≤a≤0.140 and 0.500<1-(a+b+c+d+e)<0.840 and 0≤k≤0.00100 are good. In contrast, sample No. 224 that does not contain M (Nb) and has a=0.000 has a result that the coercive force of the core is too high and the relative magnetic permeability of the core is too low. In addition, sample No. 230 in which a is too large has too large k, resulting in a coercive force of the core being too high and the relative magnetic permeability of the core being too low. In addition, except for sample No. 224, it has a structure containing amorphous. Sample No. 224 contains crystals larger than nanocrystals.
[0320] (Experimental Example 13)
[0321] In Experimental Example 13, the soft magnetic alloy powder and the toroidal core were prepared under the same conditions as those of Sample No. 217 except that the contents of B (b), P (c), Si (d), and Cr (e) were changed from Sample No. 217, and the contents of Co and Fe were changed. The results are shown in Table 17. In addition, it was not confirmed whether the microstructure of the soft magnetic metal powder including amorphous was a structure having only amorphous or a structure including heterogeneous amorphous.
[0322]
Table 17
[0323]
[0324] According to Table 17, the coercive force and relative magnetic permeability of the core of each sample whose B content (b), P content (c), Si content (d), Cr content (e), and b+c+d+e are within a specific range and satisfy 0≤k≤0.00100 are good. In contrast, the k of each sample whose B content (b), P content (c), Si content (d), Cr content (e), and b+c+d+e are outside the specific range is too large, resulting in too high coercive force of the core and too low relative magnetic permeability of the core. Among them, except for sample No. 231, they have a structure containing amorphous. Sample No. 231 contains crystals larger than nanocrystals.
[0325] (Experimental Example 14)
[0326] For sample No. 207, a part of Co was replaced with Ni, and the soft magnetic alloy powder and the toroidal core were produced under the same conditions as those of sample No. 207. The results are shown in Table 18. In addition, with regard to the fine structure of the soft magnetic metal powder, it was not confirmed whether the structure including amorphous substances had only amorphous substances or had a structure including heterogeneous amorphous substances.
[0327]
Table 18
[0328]
[0329] According to Table 18, even when a part of Co is replaced by Ni and X1 is Ni, the coercive force and relative magnetic permeability of the core of each sample whose composition is within a specific range and satisfies 0≤k≤0.00100 are good. In contrast, k of sample No. 258 with an excessively large Ni content becomes too large, resulting in an excessively high coercive force of the core and an excessively low relative magnetic permeability of the core. Among them, all samples in Table 18 have a structure containing amorphous materials.
[0330] (Experimental Example 14)
[0331] For sample No. 207, a part of Co was replaced with X3, and the soft magnetic alloy powder and the toroidal core were prepared under the same conditions as sample No. 207. The results are shown in Table 19. In addition, with regard to the fine structure of the soft magnetic metal powder, it was not confirmed whether the structure including amorphous substances had only amorphous substances or had a structure including heterogeneous amorphous substances.
[0332]
Table 19
[0333]
[0334] According to Table 19, even when a part of Co is replaced by X3, the core coercive force and relative permeability of each sample whose composition is within a specific range and satisfies 0≤k≤0.00100 are good. However, all samples in Table 19 have a structure including amorphous.
[0335] (Experimental Example 15)
[0336] For sample No. 207, a part of Co was replaced with X1 and X3, and soft magnetic alloy powder and a toroidal core were prepared under the same conditions as sample No. 207. The results are shown in Table 20. In addition, with regard to the fine structure of the soft magnetic metal powder, it was not confirmed whether the structure including amorphous substances had only amorphous substances or had a structure including heterogeneous amorphous substances.
[0337]
Table 20
[0338]
[0339] According to Table 20, even when part of Co is replaced by X1 and X3, the core coercive force and relative permeability of each sample whose composition is within a specific range and satisfies 0≤k≤0.00100 are good. However, all samples in Table 20 have a structure including amorphous.
[0340] (Experimental Example 16)
[0341] For Sample No. 207, soft magnetic alloy powder and toroidal core were prepared under the same conditions as Sample No. 207 except that the type of M was changed. The results are shown in Table 21. In addition, regarding the fine structure of the soft magnetic metal powder, it was not confirmed whether the structure including amorphous substances had only amorphous substances or had a structure including heterogeneous amorphous substances.
[0342]
Table 21
[0343]
[0344] According to Table 21, even when the type of M is changed, the core coercive force and relative magnetic permeability of each sample whose composition is within a specific range and satisfies 0≤k≤0.00100 are good. However, all samples in Table 21 have a structure including amorphous.
Claims
1. A soft magnetic alloy powder, characterized in that: Having a composition formula expressed in terms of atomic ratio (Co (1-(α+β)) X1 α X2 β ) (1-(a+b+c+d+e+f)) M a B b P c Si d Cr e S f The main components of X1 is one or more selected from Fe and Ni, X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C and rare earth elements, M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V, 0<a≤0.140, 0.180≤b≤0.250, 0.010≤c≤0.200, 0≤d≤0.250, 0.001≤e≤0.030, 0≤f≤0.010, 0.160<b+c+d+e+f≤0.430, 0.500<1-(a+b+c+d+e+f)<0.840, α≥0, β≥0, 0≤α+β<0.50, The atomic ratio of Co / Fe is 5 to 20. The soft magnetic alloy powder has a glass transition temperature Tg and a melting point Tm, And 900℃≤Tm≤1200℃.
2. The soft magnetic alloy powder according to claim 1, characterized in that: The average circularity of the powder particles contained in the soft magnetic alloy powder is 0.93 or more, and the cumulative number ratio of the powder particles from the lowest circularity to 0.50 is 2.0% or less.
3. The soft magnetic alloy powder according to claim 1, characterized in that: The average circularity of the powder particles contained in the soft magnetic alloy powder is 0.95 or more, and the cumulative number ratio of the powder particles from the lowest circularity to 0.50 is 1.5% or less.
4. The soft magnetic alloy powder according to any one of claims 1 to 3, characterized in that: The value obtained by dividing the content ratio of Co by the content ratio of B is greater than 2.000 and less than 5.
000.
5. The soft magnetic alloy powder according to any one of claims 1 to 3, characterized in that: The amorphization rate X is 85% or more.
6. A soft magnetic alloy powder, characterized in that: Having a composition formula expressed in terms of atomic ratio (Co (1-(α+β)) X1 α X3 β ) (1-(a+b+c+d+e)) M a B b P c Si d Cr e The main components of X1 is one or more selected from Fe and Ni, X3 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Cu, Bi, N, O, C, S and rare earth elements, M is one or more selected from Nb, Hf, Zr, Ta, Mo, W, Ti and V, 0<a≤0.140, 0.160<b≤0.250, 0.010≤c≤0.200, 0≤d≤0.250, 0.001≤e≤0.030, 0.160<b+c+d+e≤0.430, 0.500<1-(a+b+c+d+e)<0.840, α≥0, β≥0, 0≤α+β<0.50, The atomic ratio of Co / Fe is 5 to 20. A pressure X is applied to the soft magnetic alloy powder. P The coercivity at H , we will use the least squares method to find X P With Y H The straight line obtained by linear approximation of the relationship is represented by Y H =kX P When +l, k is 0≤k≤0.00100, where the unit of k is Oe / MPa.
7. The soft magnetic alloy powder according to claim 6, characterized in that: The amorphization rate X is 85% or more.
8. A magnetic core, characterized in that: Contains the soft magnetic alloy powder according to any one of claims 1 to 7.
9. A magnetic component, characterized in that: Contains the soft magnetic alloy powder according to any one of claims 1 to 7.
10. An electronic device, characterized in that: Contains the soft magnetic alloy powder according to any one of claims 1 to 7.
